Reoperative Surgery in Complex Crohn's Disease - Leinicke, Jennifer A.; Dietz, David W. (Clinics in Colon and Rectal Surgery, 2019)
This article provides a structured approach to the technical aspects of reoperative surgery for Crohn's disease. Specific indications for surgery including repeat ileocolic resection, Crohn's complications of ileal pouch anal anastomosis and continent ileostomy, completion proctectomy, and the role of small bowel transplant will be discussed.
Keywords: Crohn's disease; reoperative surgery; pelvic surgery; ileocolic resection; completion proctectomy; ileal pouch anal anastomosis; continent ileostomy; intestinal failure; small bowel transplantation